The Unease Between Tax Administration Innovation And Compliance: A Qualitative Study Of Taxpayers At Bangkalan Tax Office In The 2025 Transition Period - Kurniawan, Fitri Ahmad; Faraka, Fainsanu; satya angraini, merie (The International Journal of Accounting and Business Society, 2025)
Purpose — This article aims to explore the implementation of knowledge management in a multinational telecommunications subsidiary to investigate the factors that influence performance and its impact. Design/methodology/approach — Adopting a qualitative research design, this study employs an instrumental case study approach. Data were generated through in-depth semi-structured interviews with individual taxpayers, corporate taxpayers, and tax officials, and triangulated with administrative records on tax filings and revenue before and after the Coretax rollout. The analysis is guided by an integrated behavioral framework drawing on the Technology Acceptance Model and the Theory of Planned Behavior. Findings — The results show a significant decline in tax compliance during the initial phase of Coretax implementation. While the system demonstrated high usability among corporate taxpayers and tax officials by improving reporting efficiency and integration, it simultaneously resulted in low ease of use and reduced behavioral control among individual taxpayers. Complex authentication procedures, an unintuitive interface, system instability, and limited transition assistance reduced user trust and delayed compliance behavior. These results suggest that the decline in compliance reflects behavioral and institutional inconsistencies, not technological failures. Practical implications — The study highlights the need for user-segmented and adaptive digital tax implementation strategies, emphasizing usability, behavioral readiness, digital literacy support, and institutional capacity building during transition periods Originality/value — This research contributes to digital tax administration literature by demonstrating that behavioral readiness and perceived control are more decisive for compliance outcomes than system sophistication, particularly in developing-country contexts. Paper type — Case study